A comparison between ISOFIX and seatbelt installation methods for child restraint system on child occupant performance / Y. Ahmad ... [et al.] - Ahmad, Y.; A. Kassim, K. A.; M. Isa, M.H.; Mustaffa, S. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Seat belt is a proven intervention to reduce the risk of fatalities in road accidents involving adults. Nevertheless, for children, there is another prominent safety system known as child restraint system (CRS) to protect them. However CRS does not come as a standard part of the car. It needs to be installed to the car by users. Two different installation methods i.e. ISOFIX with Top Tether, and traditional three-point seatbelt were utilized in this study to compare the effectiveness of the system to reduce the injury of the child occupants. The New Car Assessment Program for Southeast Asian Countries (ASEAN NCAP) has incorporated rating assessment for Child Occupant Protection (COP) to ensure that the safety of children traveling in cars is properly highlighted. The study has made used the data from the ASEAN NCAP assessment test. Two child dummies representing 18 months and 3 years old seated in separate CRSs were subjected to offset frontal crash test at 64 km/h, as per ASEAN NCAP protocol. The accelerometers were installed at the head and chest to record the injury level of the dummies. The test parameters and same models were utilized for the comparison purpose in two crash test. Overall results, found that the combination of ISOFIX and Top Tether offered better safety performance in reducing the child occupant injuries as compared to the three-point seatbelt. ISOFIX system has improved the CRS performance for both three years old and 18 months old dummies. Head and chest resultant injuries were improved by 24% and 14% respectively for the three years old dummy. However, there is no improvement offered for vertical chest measurement. Head resultant improvement for both dummies is similar with 24% for P3 dummy and 22% for P1.5 dummy. The system is offering better chest injuries protection for the 18 months old dummy. Chest resultant is improved by 41% while chest vertical by 38%.